G363 Case reports on serious respiratory complications after renal transplant in obese children: Can these be avoided?. (7th April 2014) - Verma, P; Milford, D
Abstract : Aims: To present two obese children who suffered serious post operative respiratory complications after renal transplantation and to discuss strategies we have considered to avoid a similar problem in the future. Methods: Case 1 A 14 year old girl weighed 73 kg, BMI 35 kg/m 2 (>99.6th centile) at LRD transplant. Post operatively she was on a morphine PCA pump. Soon after surgery she developed a marked oxygen requirement (maximum FiO2 60%) that persisted for 4 days. CXR showed basal atelectasis and consolidation. She was treated with antibiotics and chest physiotherapy. The fall in creatinine was slower than expected but a satisfactory baseline value was achieved by 2 weeks. Case 2 A 13 year old girl on PD weighed 100 kg at cadaveric transplant, BMI 38 kg/m (>99.6th centile). Lung function tests before surgery were normal. Post operatively she developed a marked oxygen requirement (FiO2 70%), requiring transfer to PICU for mechanical ventilation for 5 days including high frequency oscillation. She had delayed graft function requiring CVVH followed by haemodialysis until 8 weeks post transplant and had wound dehiscence. Her creatinine 6 months post renal transplant remains elevated ( 200 µmol/L). Results: Both children had BMI >99.6th percentile, received iv opiate analgesia and suffered significant respiratory compromise post operatively which was life-threatening in the second case leading to delayed and sub optimal graft function in the short and medium term. Obese children are at risk of hypoventilation, exacerbated by reduced respiratory effort post operatively because of pain from the large abdominal wound and intravenous opiate analgesia. Although there is evidence of increased risk of adverse outcomes after renal transplant in obese adults, there are no paediatric studies. Conclusion: The prevalence of obesity in paediatric CKD patients is increasing. We propose children with CKD 4 and 5 and a BMI >98th centile are supported to lose weight and have a sleep study to identify respiratory risk. Epidural analgesia although preferable may be technically difficult in this population. We welcome debate on a proposal to exclude/suspend children from transplantation if the BMI exceeds the 98th centile.